Enforcement individual labor contracts and undeclared work - Ana Vidat (Juridical Tribune, 2016)
Failure to conclude individual employment contract as provided in the applicable legal rules in the field of legal work brings into question the concept of "undeclared work" – one of the important issues facing the Romanian society.